QUALITATIVE EVALUATION OF AFLATOXINS IN SELECTED CURRY POWDERS ON UGANDAN MARKET IN NAKIWOGO - ENTEBBE, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Joseph Gaizi; Saphan Muzoora (Student's Journal of Health Research, 2023)
Background. Mycotoxins are biologically active secondary metabolites produced by fungal species in the genera Aspergillus, Penicillium, and Fusarium and grow in a variety of foods including cereals, grains, nuts, oil seeds, fruits, vegetables, cocoa and coffee beans, wine, herbs, and spices. Several mycotoxin classes exist but aflatoxins are of great medical importance. Aflatoxins are produced by the fungi Aspergillus flavus, Aspergillus parasiticus, and Aspergillus nomius. Aflatoxins exhibit teratogenic, mutagenic, carcinogenic, immunosuppression and growth retardation properties in humans and animals. Although aflatoxins occur in various groups, aflatoxin B, is acutely poisonous. Aflatoxin occurrence in various food matrices has been reported across the globe with tropical countries bearing the most burden. In our setting, there is paucity information on aflatoxin status of food spices. In this study, 36 samples of curry powders from 16 brands in sacks and packed forms were prepared and screened for aflatoxins. Methods. The aflatoxins were extracted using 70% methanol and Chloroform for concentration. Aflatoxins were screened using thin layer chromatography and examined under Ultraviolet (UV) light at a wavelength of 366nm. Results. Results of this study indicated that 34 samples were contaminated with aflatoxin G (94.4%), followed by 6 aflatoxin B samples (16.7%). Additionally, 5 samples had both types of aflatoxins studied (13.9%). Conclusion. This study reports aflatoxin contamination in the commonly sold curry powders that are used in our homes in Uganda. Recommendations: The Uganda National Bureau of Standards needs to start periodic aflatoxin screening and quantification in the curry powders and other spices used in the production of curry powders to establish if the contamination is above the acceptable quantities.